Refiguring Law for Victims of Sexual Violence - Mukarramah, Ema (Yayasan Jurnal Perempuan, 2016)
Discourse of sexual violence bill as a special legal protection has been rolled out in accordance with various criticisms towards Criminal Code. Meanwhile, the weaknesses of substance of legislations on protecting sexual violence victim take part to strengthen the discourse. Furthermore, various facts that show obstacles experienced by sexual violence victim to achieve justice in criminal justice system become a cornerstone to raise victim-oriented perspective on legislations. This paper will elaborate urgency of sexual violence bill appearance based on availability of legislations provide protection for victim. The paper will spell out various obstacles faced by women who experienced sexual violence when seeks justice through criminal justice system as well. Moreover, the paper will look opportunity to objectify the bill based on progress of National Legislation Program.